Pengaruh Jarak Saluran Drainase Terhadap Suhu Dan Kelembaban Tanah Di Desa Teluk Empening Kecamatan Terentang Kabupaten Kubu Raya - Manurung, Alda Rahayu Felia; Arifin, Arifin; Asbanu, Govira Christiadora (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
Changes in land use in Teluk Empening have an impact on recovering infiltration capacity, loss of land cover, forest fires and drainage of peatlands, which can affect the climate. This research was conducted to determine the effect of drainage channels on the microclimate in rubber fields. The Mann Whitney test was carried out with the results that it can be concluded that there is no significant difference between the distance of the drainage canal and the high groundwater table in peatlands designated for rubber fields. Measurement of soil temperature and moisture showed that the temperature of the rubber plantation is close to drainage then the soil moisture is dry and if the measurement is far from drainage it indicates wet soil moisture. The ground water level obtained ranges from 29 "“ 64.5 cm which is influenced by the tides of the drainage channel in the morning and evening. At a distance of 20 m from the drainage canal, the groundwater level is higher than the measurements made at a distance of 100 m. This shows that the existence of drainage has a direct impact on changes in suhu and temperature of the soil